Influence of COVID-19 pandemic on the intensity of anxiety in patients with mental disorders - Đukić, Bojana; Lalovic, Nikola; Latas, Milan (Engrami, 2022)
Introduction: There is still a great lack of results regarding research on the impact of the Kovid 19 pandemic on the mental health of psychiatric patients. Objective: Assessment of the intensity of anxiety symptoms in patients with mental disorders during the Kovid 19 pandemic. Examination of the relationship between sociodemographic and clinical characteristics of patients and the intensity of anxiety during the Kovid 19 pandemic. Method: The research was conducted as a cross-sectional study by a 65 psychiatrist tasked to examin their 40 consecutive patients who had already been diagnosed with a psychiatric disorder using three assessment tools: a sociodemographic questionnaire, a clinical questionnaire and a GAD-7 to assess anxiety symptoms. Results: The sample consisted of 1,785 patients. The average value of GAD-7 score was 12.6 (SD = 4.4) and 78.2% of patients had an anxiety intensity greater than or equal to 10. Statistical analysis showed a significant difference in scores on the GAD-7 among groups of subjects who differed in some socio-demographic factors (employment, region), while such a difference was not observed in respondents who differed in gender, education, place of residence or marital status. Patients diagnosed with F3X or F4X diagnoses (mood disorders and neurotic, stressful and body manifest disorders) have the greatest anxiety, but this difference does not reach statistical significance. When asked from the Questionnaire: "During the Kovid pandemic, what worries you the most?", most respondents chose the answer: "That I or someone in the family will get sick", but respondents with the highest level of anxiety said they were worried about "something else". Conclusion: Research has shown that according to the self-assessment of their symptoms, anxiety is present in more than half of the psychiatric patients examined during the Kovid 19 pandemic. Further research in this area is needed to gain a more detailed picture basis for developing more suitable protocols for their treatment.